Effect of the uronic acid composition of alginate in alginate/collagen hybrid hydrogel on chondrocyte behavior - Zheng, Guoshuang; Xue, Chundong; Cao, Fang; Hu, Minghui; Li, Maoyuan; Xie, Hui; Yu, Weiting; Zhao, Dewei (Frontiers in Bioengineering and Biotechnology, 2023)
Developing a culture system that can effectively maintain chondrocyte phenotype and functionalization is a promising strategy for cartilage repair. Herein, an alginate/collagen (ALG/COL) hybrid hydrogel using different guluronate/mannuronate acid ratio (G/M ratio) of alginates with collagen was developed. The effects of G/M ratios on the properties of hydrogels and their effects on the chondrocytes behaviors were evaluated. The results showed that the mechanical stiffness of the hydrogel was significantly affected by the G/M ratios of alginate. Chondrocytes cultured on Mid-G/M hydrogels exhibited better viability and phenotype preservation. Moreover, RT-qPCR analysis showed that the expression of cartilage-specific genes, including SOX9, COL2, and aggrecan was increased while the expression of RAC and ROCK1 was decreased in chondrocytes cultured on Mid-G/M hydrogels. These findings showed that Mid-G/M hydrogels provided suitable matrix conditions for cultivating chondrocytes and may be useful in cartilage tissue engineering. More importantly, the results indicated the importance of taking alginate G/M ratios into account when designing alginate-based composite materials for cartilage tissue engineering.